2019
DOI: 10.3389/fpls.2019.01317
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Pathogen Resistance in Common Bean Plants by Inoculation With Rhizobium etli

Abstract: Symbiotic Rhizobium-legume associations are mediated by exchange of chemical signals that eventually result in the development of a nitrogen-fixing nodule. Such signal interactions are thought to be at the center of the plants’ capacity either to activate a defense response or to suppress the defense response to allow colonization by symbiotic bacteria. In addition, the colonization of plant roots by rhizobacteria activates an induced condition of improved defensive capacity in plants known as induced systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Alternative explanations for the Glc increase in the TFA fraction would be the accumulation of callose and/or the enrichment in a XG population tightly bound to cellulose. Both explanations seem plausible as the protective role of callose against Pph attack [ 86 ] and the function of XG by strengthening CW structure [ 63 , 64 ] have been previously reported. The CW fractionation of plants pre-treated with INA showed a noticeable displacement of matrix polysaccharides among fractions.…”
Section: Discussionmentioning
confidence: 98%
“…Alternative explanations for the Glc increase in the TFA fraction would be the accumulation of callose and/or the enrichment in a XG population tightly bound to cellulose. Both explanations seem plausible as the protective role of callose against Pph attack [ 86 ] and the function of XG by strengthening CW structure [ 63 , 64 ] have been previously reported. The CW fractionation of plants pre-treated with INA showed a noticeable displacement of matrix polysaccharides among fractions.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, to confirm that the defense response is systemic, the protective effect must be determined in organs different to those inoculated with rhizobia. These conditions are fulfilled in some of the works, confirming that rhizobia induce a defense response resembling ISR (Diaz-Valle et al 2019;Dutta et al 2008;Figueredo et al 2014Figueredo et al , 2017Figueredo et al , 2018. However, many others works were not originally designed with this aim and, therefore, fail to accomplish some of the requirements.…”
Section: Isr -Like Responses Displayed By Rhizobiamentioning
confidence: 78%
“…Many works provide data supporting the notion that inoculation of legumes with rhizobia results in the induction of an increased defense response effective against diverse pathogens (necrotrophs, biotrophs) and herbivores (Arfaoui et al 2005(Arfaoui et al , 2006(Arfaoui et al , 2007Chakraborty and Chakraborty 1989;Diaz-Valle et al 2019;Dutta et al 2008;Figueredo et al 2014Figueredo et al , 2017Kalantari et al 2018;Mabrouk et al 2007;Osdaghi et al 2011;Rabie 1998;Smigielski et al 2019) (Table 1). This effect was also observed in non legumes after rhizobial inoculation (Mishra et al 2006;Reitz et al 2000).…”
Section: Isr -Like Responses Displayed By Rhizobiamentioning
confidence: 86%
“…phaseoli significantly reduced the disease severity of CBB under both greenhouse and field experiments. Díaz-Valle et al (2019) delineated that the inoculation of common bean with Rhizobium etli inhibited halo blight severity as compared to plants not inoculated with the symbiont and indicated that the size of foliar pathogen lesion was 75% lesser in the Rhizobium etli-treated plants than in the uninoculated plants. Osdaghi et al (2011) assessed the inoculation of the Rhizobium leguminosarum bv.…”
Section: Rhizobia As a Biocontrol Agent Of Plant Diseases Caused By Bacteriamentioning
confidence: 99%
“…viciae, Rhizobium meliloti, Rhizobium trifolii, Sinorhizobium meliloti, and Bradyrhizobium japonicum have been reported to produce antibiotics and cell-wall-degrading enzymes that can hinder the phytopathogenic bacteria (Gopalakrishnan et al, 2015). Díaz-Valle et al (2019) also showed that rhizobial inoculation facilitated greater and more rapid activation of defense-related genes following infection with the pathogenic bacteria and suggested that inoculation is imperative for a cellular mechanism of ISR in plants.…”
Section: Rhizobia As a Biocontrol Agent Of Plant Diseases Caused By Bacteriamentioning
confidence: 99%